The prevalence and risk of urinary tract infection in malnourished children: a systematic review and meta-analysis - Samuel N. Uwaezuoke; Ikenna K. Ndu; Ikenna C. Eze (BMC, 2019)
Abstract Background There are vast differences in prevalence rates of urinary tract infection (UTI) reported among malnourished children globally. We conducted a systematic review and meta-analysis to provide estimates of pooled prevalence of UTI among these children and combined UTI risk in comparison with their well-nourished counterparts. Methods We systematically searched electronic databases (MEDLINE, EMBASE, ISI Web of Science and African Journals Online; date of the last search: 22 December 2018) for studies reporting either the prevalence of UTI in malnourished children or parallel healthy controls. Eligible primary studies were observational studies of children in English Language reporting UTI prevalence with background malnutrition or with enough data to compute these estimates, as well as studies which reported at the same time UTI prevalence in healthy controls. We synthesized published prevalence rates or associations (odds ratios [OR]) between malnutrition and UTI and their 95% confidence intervals (CI) using random effects meta-regression and explored potential heterogeneity determinants using meta-regression analysis. This review is registered with PROSPERO, number- CRD42018084765. Results We included 26 cross-sectional and 8 case-control studies reporting on UTI prevalence in malnourished children, and in malnourished children vs. healthy controls, respectively. The pooled prevalence of UTI in 3294 malnourished children was 17% (95% CI, 13, 21%). Heterogeneity was high (I2 = 87.6%; Tau2 = 0.06) as studies varied in their sample size, degree of malnutrition, and study period. Multivariate meta-regression model, including these factors, explained 34.6% of the between-study variance. Pooled OR of UTI in association with malnutrition in 2051 children (1052 malnourished children vs. 999 controls) was 2.34 (95% CI, 1.15, 3.34), with lower between-study heterogeneity (I2 = 53.6%; Tau2 = 0.47). Conclusions UTI is more prevalent in malnourished children than in their well-nourished counterparts. Screening and treatment for UTI should be incorporated in the management protocol of malnourished children to improve disease outcomes.